THE ANALYSIS OF THE CORRELATION BETWEEN HABIT IN LISTENING TO ENGLISH SONGS AND GRADE ELEVEN STUDENTS’ VOCABULARY ACQUISITION - Nurul Hasanah Fajaria (Lingua, 2017)
This research entitled “The Analysis of The Correlation Between Habit in Listening to English Songs And Grade eleven students’ Vocabulary Acquisition At SMA Yadika 8 Bekasi” the aim of the research is to investigate whether or not the correlation between habit in listening to English songs and grade eleven students’ vocabulary acquisition. The total number of sample is 24 students in class XI IPA 4, it was taken using cluster random sampling. The location of this research was SMA Yadika 8 Bekasi. The research methodology adopted was correlational method, and the research design was Expost facto design. To collect the data, the students were given objective test and questionnaire, each 30 and 20 items. The data was analyzed by SPSS 24 Pearson’s product moment correlation. It showed that Rxy = 0,593 is higher than the critical value rtable (at the significant of 5% and df is 24 – 2 = 22), namely 0,432. It means that there is significant correlation between habit in listening to English songs and grade eleven students’ vocabulary acquisition.